VOLUMETRIC COLOR APPROACH AS APPLICATION OF VISUAL COLOR IN SPACE ZONING CONCEPT - Qobus Tsaqif; Ully Irma Maulina Hanafiah (Ide dan Dialog Desain Indonesia (Idealog), 2020)
In the development of interior design, many are applied to create an atmosphere that can create aesthetics and convenience for users. A design can develop through interior elements, especially through color and shape. In a space design with various functions it creates its own zoning at various activities. The emphasis on zoning can be developed through an interior design with the concept of distinct space, by applying various elements that can distinguish space, such as color elements. Volumetric Color approach which uses colors to create a volume of space in an area by using the same color in all interior elements. The difference in color and shape of space creates zoning and function in space to be more specific. In addition to zoning, the use of different and striking colors can provide vocal points and aesthetics in space. The purpose of this descriptive-analysis research is to make a systematic, factual and accurate description, picture, or painting of a case study producing a space with attractive volumetric colors, and as an identity in space. The results of this study can play a role in interior design in the use of color not only as aesthetics of the space, also can provide convenience for users to recognize areas that exist with different functions. In addition, the use of colors in accordance with the function of the area can also be adjusted to affect the psychological space that can have a positive impact on space. Keywords: Volumetric Color, Zoning of Space, Limitation of Space Functions